Relationship dynamics and perpetration of intimate partner violence among female Chinese college students - Du, Jingshuai (Kansas State University, 2019)
In China, most violence studies focus on male intimate partner violence (IPV) perpetration and female victimization, and studies on dating violence and female IPV perpetration are less common. Although female IPV perpetration and gender symmetry in IPV in China has surfaced with very recent research, there have been limited studies examining the factors related to female perpetration in dating relationships in China. In the current research, we aim to examine how relationship factors, including anger management, communication problems, relationship conflict, and relationship distress are linked with female physical and psychological IPV perpetration. We included 857 female college students in three regions in China from the International Dating Violence database. A single path analysis model was performed to answer three questions: 1) Is the participants’ level of anger management skills associated with lower levels of physical and psychological IPV perpetration; 2) Is the participants’ level of communication problems, relationship conflict, and relationship distress associated with higher levels of physical and psychological IPV perpetration and; 3) Does the participants’ level of anger management skills moderate the negative effects of relationship conflict and distress in predicting their self-reported level of IPV perpetration. We found that Chinese college women’s anger management skills and communication problems were both significantly associated with physical and psychological abuse on both minor and severe levels, relationship conflict was significantly associated with minor physical, minor psychological and severe psychological abuse, and anger management skills moderated the negative effects of relationship conflict on female IPV perpetration. Our findings suggest that it may be important to explore the role of college women’s anger management skills, communication problems and conflict resolution skills in their dating relationships, as well as to develop female-based intervention programs to increase Chinese college women’s anger management, communication skills and conflict resolution skills, in order to reduce their levels of IPV perpetration.
Keywords: Intimate partner violence; Female perpetration; Relationship dynamics; China; College students